The Art of Creative Conflict Resolution: A Critical Evaluation of Approaches to Post-Conflict Reconstruction in Northern Uganda - Lindsay McClain (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2010)
The Acholi of northern Uganda, whose cultural heritage is rich in literature and the performing arts, are emerging from more than two decades of war, and there is a desire and need to nurture a culture of peace. Over the last four years, numerous organizations and individuals in Uganda have incorporated the arts into conflict resolution, community reconciliation, and psycho-social healing. These creative approaches, designed to encourage reconciliation, have varied enormously, as have the degrees to which northern communities have accepted and taken ownership of them. A careful analysis of their resonance and impacts has been largely overlooked and underrepresented in scholarship. Therefore, based on research conducted in Uganda from 2007 to 2009, the influx of projects involving the creative arts are comparatively and critically evaluated by assessing what is global, what is local, and what is gender-, place-, and age-specific, as well as how the projects’ funding sources affect their short- and long-term sustainability. This paper concludes with recommendations for future programs rooted in the arts and possible implications of this evaluation for other post-conflict reconstruction strategies in Africa today.
Keywords: Undergraduate Research; Pursuit